Competitive complex of machinery and technologies for the production of grain and feed - N. K. Mazitov; R. L. Sakhapov; Yu. Kh. Shogenov; L. Z. Sharafiev; Yu. S. Tsench; I. R. Rakhimov (Аграрная наука Евро-Северо-Востока, 2019)
The current situation in agricultural production is challenging. During the last 2 decades, the agrarian production system has been deteriorating. It concerns crop rotations, moisture accumulation and moisture conservation technologies, ways of increasing soil fertility and growing environmentally friendly grain, reducing production costs and increasing product profitability. But there are forced late sowings and artificial “drought”. All this provides reasons to consider domestic breeding and seed production obsolete and to introduce the foreign analogue, which has planned negative impacts not only on quantitative, but also on qualitative safety. The article provides the solution to this major strategic problem. Under the research program of the Russian Academy of Agricultural Sciences, a highly competitive technology for the production of grain and fodder was developed on the basis of only domestic equipment that 2-5 times predominates over the best foreign analogues in functional indicators. It was confirmed by a number of state tests in 1990-2016 and approved by numerous meetings of the Scientific and Technical Council of the Ministry of Agriculture of the Russian Federation, RAS. The units of domestic tractors and functional machines that can compete with the best foreign counterparts have been developed.